MyBioethics: How Ed-Tech Enables Discovery-Driven Empirical Bioethics Research - Janhonen, Joel; Värttö, Mikko; Saxén, Heikki (Springer Nature, 2025)
Digital tools have granted new opportunities to engage people with bioethical discussion and rehearsed decision-making. The ongoing development of the MyBioethics mobile application links these together within a digital space designed to encourage deliberation and research participation by inviting users into the process of discovery. Besides educational purposes, this has enabled a unique way to gather real-world observations. A research procedure was designed to harness the functionality of a mobile application. Quantitative data was generated by dilemma scenarios and integrated surveys that measure and inform users about their psychological and epistemic tendencies. The resulting analysis enabled the possible influence of these factors on moral judgment formation to be investigated—leading to the preliminary identification of prospective relationships. The adopted methodology is crowdsourced and explorative. We seek to generate hypotheses as well as facilitate ethical reflection among users. This work is a proof-of-concept. The main finding is the tentative confirmation of the approach. A digital teaching tool can function to advance empirical bioethics research. The gathered data unveiled prospective areas of academic interest and yielded observations that may contain valuable reflective insights for individual end users. Digital bioethics brings along new opportunities to engage a diverse user base in a way that provides educational resources, challenges ethical preconceptions and intuitions, allows inclusion in research efforts, and encourages autonomous decision-making. Ed-tech applications appear suitable for investigating personal tendencies that are influencing our moral judgments. Digital environments could be designed to surface unarticulated factors behind our held positions and challenge unquestioned moral notions.